Cambios en las proteínas asociadas a estrés oxidativo de Apis mellifera expuestas al insecticida sistémico Imidacloprid. (2023)
The increase in agricultural crops has brought with it the increase in the use of insecticides, however, its application has collaterally impacted pollinating insects. Insecticides induce oxidative stress in bees, but the reason why it occurs has not yet been fully elucidated, which is why this study sought to describe the interactions between the insecticide imidacloprid with catalase, glutathione peroxidase and superoxide dismutase using molecular docking, as well as evaluating the expression changes of proteins related to oxidative stress of protein extracts from A. mellifera.